Pedagogical interventions in augmentative and alternative communication (AAC): therapeutic benefits in healthcare and quality of life. A systematic review - David Gómez-Asencio; Francisco-Javier Gago-Valiente; Francisco-Javier Gago-Valiente; Cristina Arana-Álvarez; María-Isabel Mendoza-Sierra; María-Isabel Mendoza-Sierra; María-José López-López; Emilia Moreno-Sánchez; Emilia Moreno-Sánchez (Frontiers in Communication)
IntroductionThe scientific literature was reviewed with the aim of to identify and synthesize empirical studies reporting the application of AAC strategies in hospital-based educational and healthcare environments for individuals with communication impairments.MethodsThe article search was carried out in the WOS, Scopus and PubMed databases, and it was limited to studies published in the last 10 years. The study was registered in the International Prospective Register of Systematic Reviews (PROSPERO), and its quality was evaluated with the Effective Public Health Practice Project (EPHPP) instrument.ResultsAmong the 256 articles that were initially selected, only a total of 10 studies met the established eligibility criteria after performing a more exhaustive analysis with abstract and full text reading. The results show a positive relationship between the use of AAC and improvements in communication skills in the identified populations.DiscussionDifferent AAC strategies can be applied and employed in people with communication difficulties, thereby improving their quality of life and that of their environment. Educational centres can be true learning scenarios to favour the maximum psychosocial potential of their students. Moreover, these resources can also be used with clinical and/or therapeutic purposes in healthcare.